INTEGRITAS CHAIN OF CUSTODY PADA PEMERIKSAAN BUKTI DIGITAL - Mustafa, Cecep (Ikatan Hakim Indonesia (IKAHI), 2024)
In this paper, the author discusses the urgency of implementing a digital forensic readiness framework used by the Supreme Court of Indonesia and stakeholders to identify, collect, and maintain digital evidence and respond faster during the post-incident phase than usual by initiating forensics investigations. Digital photography, as soon as possible, upon incident detection, gets digital evidence first. The proposed Guideline has been created by considering the principles of digital forensic readiness requirements based on ISO/IEC 27043.